Syngonium podophyllum Leaf Extract Mediated Synthesis and Characterization of Gold Nanoparticles for Biosensing Potential: A Sustainable Approach - Srivastava, Saumya; Pandey, Anjana (Current Nanoscience, 2021)
Background: The existing methods of analyte detection by various biochemical processes have certain drawbacks including nonlinearity and detection limits. The nanotechnology has paved a way for the development of new devices i.e., nano-biosensors, by amalgamation of nanoparticles with recognition elements. These nano-biosensors have the capabilities to overcome the drawbacks of conventional methods. Objectives: Present study was planned to analyze the biosensing potential of indium tin oxide (ITO) electrode modified with gold nanoparticles synthesized using aqueous extract of S. podophyllum. Methods: In present study, first time rapid green synthesis of gold nanoparticles from leaf extract of Syngonium podophyllum is reported. The synthesized nanoparticles were then characterized physically by UV-Visible spectroscopy, particle size analysis, fluorescent spectroscopy, Fourier transform infrared spectroscopy and transmission electron microscopy (TEM), and HR (High resolution)-TEM. Results: The particles were observed to be in average size range of 30-70 nm. Furthermore, the ITO electrode was modified with the prepared nanoparticles and analyzed by ellipsometry. The electrochemical characteristics of the modified electrodes were analyzed by cyclic voltammetry. Conclusion: The results exhibited a higher current gain, thus signifying a higher signal amplification at the electrodes and paves the way for their use in electrochemical nanobiosensors.
Keywords: TEM